The Realities Of The Agricultural Market - Покальчук, М. Ю. (Theory and practice of jurisprudence, 2016)
Problem setting. Government policy on the development of agricultural market is defined by the Law of Ukraine "On the Fundamentals of State Agricultural Policy for the period up to 2015" dated 18 October 2005 р., № 2982-IV (hereinafter - the Law). Of the said Act could be concluded that the State’s agricultural policy is a set of legal, organizational and economic measures aimed at improving the efficiency of the agricultural sector of the economy, solving social problems of the rural population and ensuring integrated and sustainable rural development (Art. 1 of the Act). Basic principles of state agricultural policy aimed at sustainable development of the agricultural sector in the national economy for the period up to 2015, consistency and comprehensiveness in the implementation of measures to implement the state agricultural policy to all government agencies and local authorities. The purpose of this article is to clarify the nature of the legal institution as the agricultural market, identify and study the elements of its structure. State agricultural policy based on national priorities and takes into account the need to integrate Ukraine into the European Union and the world economic space. An important role in the organization of the agricultural market belongs market infrastructure institutions that are designed to act as a generator of demand for agricultural products and in accordance with its price. These include: agricultural exchanges, trading houses, auctions, wholesale and retail markets, etc., on which the development of a public policy. Characterize their legal status in detail. Article 17 of the Law of Ukraine "On State Support of Agriculture of Ukraine" provides a definition of the Agrarian Exchange and the basic principles of its activity, according to which such exchange is a non-profit (non-commercial) enterprise. The founder of the Agrarian Exchange may be Cabinet of Ministers of Ukraine, represented by the Agrarian Fund. In this case, the Cabinet of Ministers of Ukraine shall founding contribution to the authorized fund (capital) of such agrarian exchange in an amount equal to the minimum requirements in the statutory fund resident bank, which has the license for the full scope of banking operations and manages the property represented by the Agrarian Fund. Members of the Agrarian Exchange may only residents. Under the Agrarian Exchange can understand the specific entity that participates in the organized market of certain agricultural products as set out by law. The Law of Ukraine "On State Support of Agriculture of Ukraine", according to the Cabinet of Ministers of Ukraine "On Agricultural Fund" of 6 July 2005 р., № 543, was created by the Agricultural Fund, which is a specialized agency of the state budget authorized by the state to implement price policies in the agricultural sector. Under the provisions of these legal acts, the Agrarian Fund belongs to the Ministry of Agrarian Policy and Food of Ukraine, is accountable to and controlled by him. The Fund is a budgetary organization has its own estimates, invoices and performs non-profit activities within the limits set by law. The role and importance of the Agrarian Fund in the modern state agrarian policy is outstanding and highlighted its objectives. Another subject of the agricultural market in Ukraine are the wholesale markets, the legal status of which is defined by the Law of Ukraine "On the wholesale markets of agricultural products" of 25 June 2009 р., № 1561-VI. According to the latter, the wholesale market for agricultural products is defined as a legal entity, the subject of which is to provide the ambassador that are engaged in the wholesale trade in agricultural products, and which as prescribed by law given the status of a wholesale market of agricultural products. The purpose of the establishment and functioning of agricultural and trade houses in Ukraine is accelerating and deepening agrarian reform by creating the market environment, the development of commodity-money relations, more advantageous realization of production and improvement of logistics agricultural producers. The legal basis for the emergence of agricultural and trade houses was at one time (already expired) Order of the Ministry of Agriculture and Food of Ukraine and the Ukrainian Academy of Agrarian Sciences of March 18, 1996 р., № 85/17 approving the Model Regulations on inter-regional and regional agro. Today the sale of agricultural products for profit is a necessary final stage of activity of any agricultural commodity. It is therefore very widespread experience fairs agricultural products that represent the movement of goods and money, the buyer gets what he needs, and the seller - financial reward for their work, compensation costs for production and financial resources needed for the next production cycle (seeds purchase, lease the required equipment, etc.). But, auctions and commodity exchanges are relatively permanent measures and institutions, exhibitions and fairs are held less frequently, but with a clear frequency. Exhibitions of agricultural and agro-industrial products and a major event is the biggest exhibition "Agro - ...". It is held annually and allows producers to sell their products to customers (wholesale party). However, its main purpose - to demonstrate the achievements of the economy, establishing contacts with foreign partners, solving industry problems (during exhibitions conferences, "round tables" with a discussion of various issues of agriculture and the agro-industrial complex of Ukraine, the market of agricultural products). Fairs are primarily entertainment and tourist activities in the second - trade. The successful and regular conduct of such activities, not only is the final element of the agricultural and agro-industrial complex of Ukraine, but also elevates the authority of the state, facilitates the development of tourism resources and cultivate patriotism, preserve the good old tradition of the people and upload them young. Exhibition and fair activity in Ukraine is regulated, in particular, by the Cabinet of Ministers of Ukraine "On improvement of exhibition and fair activity in Ukraine" dated 22 August 2007 р., № 1065, approving the Concept of exhibition and fair activities and the Order of the Ministry of Agrarian Policy of Ukraine "On improvement of exhibition and fair activities in the Agriculture Ministry ’of 27 March 2008 р., № 183. The study of the current state of the agricultural market allows conclude that at present the legislation defining the legal status of the components of the agricultural market, namely: the Agricultural Exchange, the Agricultural Fund, the wholesale markets of agricultural products, agricultural and trade houses exhibitions, Fair of agricultural products is not perfect, and not always correspond to the realities of today. It is our belief system analysis and reform of legislation in a position to bring the agricultural market of Ukraine at the leading place in the world economy. To this end, for each of the entities involved in the agricultural market needs to develop a new individual legal act defining its legal status and update existing legislation. Keywords: agricultural market, the Agrarian Fund, the Agricultural exchanges, trading houses, auctions, agricultural products.